2004
DOI: 10.1152/ajpendo.00228.2004
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal intracerebroventricular exposure to leptin causes an altered adult female phenotype

Abstract: We investigated the effect of daily intracerebroventricular (ICV) leptin administration (neonatal age 2-7 days) on hypothalamic neuropeptides (neuropeptide Y, ␣-melanocyte-stimulating hormone) that regulate food intake, body weight (BW) gain, and the metabolic/hormonal profile in suckling (8 and 21 days) and adult rat (35, 60, 90, and 120 days). ICV leptin (0.16 g ⅐ g BW Ϫ1 ⅐ dose Ϫ1 ; n ϭ 70) led to a postnatal decline in BW (P ϭ 0.0002) that persisted only in the adult females (P ϭ 0.002). The postnatal decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
(155 reference statements)
2
14
0
Order By: Relevance
“…Similarly, this same phenomenon is observed in human studies with hyperleptinemia in infants from gestational undernutritioned or diabetic mothers [48]. Further, intracerebroventricular leptin administration to neonatal rats altered adult female phenotypes, including a reduction in body mass and food intake [49]. These studies suggest that perinatal leptin plays the critical role in programming adult metabolic phenotypes although serum leptin showed different responses to early nutritional environments.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, this same phenomenon is observed in human studies with hyperleptinemia in infants from gestational undernutritioned or diabetic mothers [48]. Further, intracerebroventricular leptin administration to neonatal rats altered adult female phenotypes, including a reduction in body mass and food intake [49]. These studies suggest that perinatal leptin plays the critical role in programming adult metabolic phenotypes although serum leptin showed different responses to early nutritional environments.…”
Section: Discussionsupporting
confidence: 67%
“…Similar effects were observed when leptin was injected intracerebroventricularly, associated with glucose intolerance in females [65] . In the same way, hyperinsulinemia and lower adiponectinemia were found in adult offspring whose mothers had prolactin inhibition during the last 3 days of lactation [32] .…”
Section: Programming Diabetes Mellitussupporting
confidence: 70%
“…However, they did not display higher fat depots and this could be better understood considering that they presented thyroid hyperfunction [62,63] and higher catecholamine secretion [64] as will be discussed later. Those effects seems to depend on the administration route, since Varma et al [65], who injected leptin intracerebroventricularly, observed a programming effect with lower body weight and food intake, hypoleptinemia, hyperinsulinism and an impaired glucose tolerance test but only in females. We think that our model provides a better reproduction of the increase in leptin that occurs in obesity or by leptin transfer into the milk since the increase occurs peripherally and can modulate leptin receptors.…”
Section: Leptin and Body Weight Programmingmentioning
confidence: 99%
“…We demonstrated that the serum concentration of leptin was altered by manipulation of maternal protein intake. Leptin during the lactation period is a candidate for programming of the appetite system [11,25,26]. Postnatal low protein animals had substantially reduced blood leptin concentration compared with control animals under both fed and fasted conditions.…”
Section: Discussionmentioning
confidence: 99%